A survey of the knowledge, attitude, and practice of using probiotics for oral health among dental students in Kerala - Rajeev, Gayathri; Jacob, Arun; Santhosh, Sandra; Roshni; Vijayan, Anjitha S.; Puthukkodan, Reshma; Geetharani Vijayakumar, Sangeetha (International Journal Of Community Medicine And Public Health, 2024)
Background: Widespread prevalence of dental caries, particularly in developing countries, poses a major public health challenge. Traditional approaches using fillings and remineralizing agents have limitations. Probiotics offer a potentially self-administered, multifaceted alternative for both preventing and managing caries, with additional health benefits beyond oral health. Methods: A cross-sectional study with a validated questionnaire was conducted among 308 final-year students and 292 interns from dental colleges in Kerala. Data were analyzed using descriptive and inferential statistics. Results: Over 74% of interns and final-year students recognized probiotic benefits. Awareness about prebiotics was limited in both groups (59.7% and 62.3%, respectively). Notably, 65.6% of students and 72.6% of interns demonstrated knowledge about the probiotic potential of streptococcus strains. Almost 43% of students and 55% of interns reported current or past probiotic use and recommendations. A substantial majority in both groups (over 87%) expressed willingness to try recommended probiotic products. Notably, 47.4% of final-year students and 44.5% of interns had not used probiotics therapeutically, with gastrointestinal issues being the primary indication for those who did. Conclusions: High awareness of probiotics with knowledge gaps in certain areas (e.g., prebiotics) was observed. The majority showed a willingness to utilize probiotics in their practice. Educational interventions focused on these areas could equip dental professionals to provide informed advice and recommendations about probiotics to their patients.